Passive strategies used in Southern Portugal vernacular rammed earth buildings and their influence in thermal performance - Fernandes, Jorge Emanuel Pereira (2019)
In Portugal, there is a lack of quantitative studies on the thermal performance of earthen buildings. This paper aims at contributing to this research context by studying site-specific strategies, and the thermal performance and comfort conditions of a rammed earth building located in southern Portugal. The study is based on objective and subjective assessments and consists of assessing the hygrothermal conditions, thermal comfort levels and analysing the occupants? perception regarding thermal sensation. The results showed that the strategies used are closely related to local conditions, mitigating the effects of high summer temperatures and ensuring a good summer thermal performance by passive means alone. During the summer monitoring, results showed that the building stayed most of the time (80%) in Category I (high level of expectation) and the remaining time in Category II, according to the classification method defined by the standard EN15251. During the winter period, the building had the worst performance, being necessary a heating system to guarantee comfort conditions. Additionally, the results showed that the good thermal performance of the case study depended more on the high thermal inertia than on the U-value of the envelope. Limitations and advantages of the use of earthen construction elements are discussed.